(untitled) (International Journal of Engineering and Computer Science, 2019)
Digital platforms are increasingly relying on third-party data to inform their product-service development. Open data initiatives have emerged in an attempt to democratize data, while platform-based companies have resurrected two-phase marketing to inform pricing. Because many users are still unaware of the potential value of their data, and as a result are taking no action to solicit better services, it is not surprising that editing third-party data is not a priority for them. User-producers’ larger data pool does not ensure a fairer and more robust data economy, as algorithmic power remains an issue for all actors and the origins of the potential infidelity remains hidden. The future of efficiency is neither having platforms give lead users data that is unstructured and unfiltered, nor giving platform companies the data of the general public. The approach will need to focus on the consumers and on actionable insights based on their feedback, while also putting the focus on consumers’ reservations about relinquishing feedback [1]. In addition to the exterior issues of the feedback mechanisms, there are potential adjustments in the feedback processes to improve engagement. Certain adjustments relate to the initial experience design of seeking and providing feedback by the consumers, while others concern the tools and prompts built into the platform feedback systems. The design includes both the design principles that can be adjusted to create immediate appeal and facilitate involvement, and design criteria that require more extensive testing and calibration before reaching critical levels of adjustment and widespread applicability while still being arguably necessary for any digitally enabled system.